Conflicts in UN reform negotiations: Insights into and from the review of the High-level Political Forum on Sustainable Development - Marianne Beisheim (Stiftung Wissenschaft und Politik (SWP), 2021)
The UN High-level Political Forum on Sustainable Development (HLPF) is widely appreciated as a venue where representatives of the member states, the UN system and stakeholders can discuss the implementation of the 2030 Agenda and its Sustainable Development Goals (SDGs). This study analyses the negotiations on the HLPF review conducted in 2020/21 under the UN General Assembly. The intended strengthening of the HLPF was blocked by numerous conflicts over environmental and development issues as well as overarching conflict lines concerning the international order. Lessons should be drawn for future UN reform processes. The resulting resolutions largely confirm the status quo. The few incremental improvements should now be realised. The German government and the EU should work to improve the preparation and follow-up for the HLPF meeting in July 2022. The new Coordination Segment of the UN Economic and Social Council (ECOSOC), which meets for the first time in February 2022, offers an important opportunity. The German government and the EU should prepare ambitious annual UN strategies that also cover their work in ECOSOC and the HLPF. The identified conflict themes should be taken into consideration. The UN Secretary-General's report "Our Common Agenda", requested by the member states and published in September 2021, creates a window of opportunity for progress on UN reforms. By early 2024, when the next HLPF review is due, the German government and the EU should have developed reform proposals. They should communicate these in good time in the Alliance for Multilateralism and seek to build coalitions of the willing.
Keywords: 320